Innovating and adapting in pediatric pulmonology and sleep medicine during the COVID‐19 pandemic: ATS pediatric assembly web committee consensus statement for initial COVID‐19 virtual response. Issue 2 (23rd December 2020) - Taylor, Jane B.; Oermann, Christopher M.; Deterding, Robin R.; Redding, Gregory; Davis, Stephanie D.; Piccione, Joseph; Moore, Paul E.; Kupfer, Oren; Santiago, Maria Teresa; Rosenfeld, Margaret; Ingram, David G.; Ross, Kristie; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) has been an unprecedented and continuously evolving healthcare crisis. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) spread rapidly and initially little was known about the virus or the clinical course for infected children. In the United States of America, the medical response has been regionalized, based on variation in community transmission of the virus and localized outbreaks. Pediatric pulmonary and sleep divisions evolved in response to administrative and clinical challenges. As the workforce transitioned to working remotely, video conferencing technology and multicenter collaborative efforts were implemented to create clinical protocols. The COVID‐19 pandemic challenges the framework of current medical practice but also highlights the dynamic and cooperative nature of pediatric pulmonology and sleep medicine. Our response to this pandemic has laid the groundwork for future challenges.